2018
DOI: 10.1111/echo.14103
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical cardiac disease in ankylosing spondylitis

Abstract: Subclinical cardiac dysfunction occurs in AS patients despite well controlled musculoskeletal disease. Aortic stiffness and LVGLS increases in AS patients. Anti-TNF biological agents may somewhat protect arterial compliance. We believe that all AS patients should be investigated for cardiac dysfunction and followed up accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“… 12 Selin Ozen and colleagues also demonstrated that increased left ventricular global longitudinal strain is seen in AS patients. 13 Apart from subclinical myocardial dysfunction many studies have also showed subclinical atherosclerosis in AS patients. 11 15 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Selin Ozen and colleagues also demonstrated that increased left ventricular global longitudinal strain is seen in AS patients. 13 Apart from subclinical myocardial dysfunction many studies have also showed subclinical atherosclerosis in AS patients. 11 15 …”
Section: Discussionmentioning
confidence: 99%
“…23 Since ankylosing spondylitis patients are 60% more likely than the general population to be hospitalised with (aortic) valve disease, it appears that aortic regurgitation might still be an important problem. 24 In an adult study, Ozen et al 25 evaluated aortic stiffness as a measure of cardiac disease using arterial stiffness and the associated haemodynamic changes for an independent predictor and risk factor for cardiovascular mortality and morbidity. They suggested that arterial stiffness has been directly associated with systolic hypertension, coronary artery disease, stroke, and cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…The main imaging modalities used for evaluation of myocardial status in SpA include echocardiography and cardiovascular magnetic resonance (CMR). Subclinical cardiac dysfunction was identified in AS patients despite well controlled musculo-skeletal disease, using echocardiography [59]. Furthermore, aortic stiffness and left ventricular global longitudinal strain (LVGLS) were increased in AS patients [59].…”
Section: Role Of Imaging For Cardiac Assessment In Spamentioning
confidence: 99%
“…Subclinical cardiac dysfunction was identified in AS patients despite well controlled musculo-skeletal disease, using echocardiography [59]. Furthermore, aortic stiffness and left ventricular global longitudinal strain (LVGLS) were increased in AS patients [59]. In another echocardiographic study, early, subclinical myocardial dysfunction was observed in inflammatory joint disease (IJD) patients with preserved left-ventricular ejection fraction, but without traditional CV risk factors.…”
Section: Role Of Imaging For Cardiac Assessment In Spamentioning
confidence: 99%